2007
DOI: 10.1002/ejoc.200601054
|View full text |Cite
|
Sign up to set email alerts
|

Rubromycins: Structurally Intriguing, Biologically Valuable, Synthetically Challenging Antitumour Antibiotics

Abstract: Although known for more than 50 years the rubromycin family still constitutes a fascinating class of antitumour antibiotics. They are characterized by a challenging molecular architecture with the central spiroketal unit as the key feature and possess highly attractive biological properties. After a short treatment of the history of their isolation, structural elucidation and biosynthesis, their biological activities will briefly be summarized. This review strongly emphasizes the synthetic efforts aimed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 45 publications
0
70
0
6
Order By: Relevance
“…This involves the creation of both the ethereal spiroketal bonds through sequential additions of the alcohols under reversible conditions to furnish the thermodynamic diastereomer. While this method has been successfully applied to the synthesis of numerous aliphatic spiroketals, it has been shown that many phenols lack the nucleophilicity needed to undergo this transformation [3]. In light of this diminished reactivity, we chose to take an orthogonal approach predicated upon successful cycloaddition reactions employing exocyclic enol ethers.…”
Section: Introductionmentioning
confidence: 99%
“…This involves the creation of both the ethereal spiroketal bonds through sequential additions of the alcohols under reversible conditions to furnish the thermodynamic diastereomer. While this method has been successfully applied to the synthesis of numerous aliphatic spiroketals, it has been shown that many phenols lack the nucleophilicity needed to undergo this transformation [3]. In light of this diminished reactivity, we chose to take an orthogonal approach predicated upon successful cycloaddition reactions employing exocyclic enol ethers.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples include heliquinomycin (4), [4] an inhibitor of DNA helicase, [5] and purpuromycin (5), [6] a potential topical agent for vaginal infections (Scheme 1). [7] Much effort has been devoted to the synthesis of these compounds, [8][9][10][11][12][13][14][15][16] and special attention has been focused on the preparation of the vital bisbenzannelated spiroketal core structure I. [8][9][10][11][12][13] The reported methods are based on the acidcatalyzed spiroketalization of ketones [10][11][12] or a hemiketal, [9b] the haloetherification of a benzofuran, [9a] or the oxidative [3+2] cycloaddition of an enol ether with a b-diketone.…”
mentioning
confidence: 99%
“…[7] Much effort has been devoted to the synthesis of these compounds, [8][9][10][11][12][13][14][15][16] and special attention has been focused on the preparation of the vital bisbenzannelated spiroketal core structure I. [8][9][10][11][12][13] The reported methods are based on the acidcatalyzed spiroketalization of ketones [10][11][12] or a hemiketal, [9b] the haloetherification of a benzofuran, [9a] or the oxidative [3+2] cycloaddition of an enol ether with a b-diketone. [13] However, multiple steps were required to build up the ketals I from smaller fragments, and the applicability of these methods to a wide range of analogues has not been demonstrated.…”
mentioning
confidence: 99%
“…The synthesis of members of rubromycin family of bis(benzannulated) spiroacetals under acid-catalyzed conditions have been hampered by the complex Scheme 16 Kozlowski et al's dehydrative spirocyclization studies toward purpuromycin [62] stereoelectronic properties of naphthalene and/or isocoumarin precursors [58][59][60]. In their formal synthesis of γ-rubromycin 58, Brimble et al [61] successfully balanced these factors to access the bis(benzannulated) core via dehydrative spirocyclization of a dihydroxyketone 59 (Scheme 15).…”
Section: Bis(benzannulated) Spiroacetalsmentioning
confidence: 99%